E.X.P.E.R.T. role play technique for workplace readiness - Rozmel Abdul Latiff,; Zarina Othman,; Khaidzir Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Role plays and the instructional methods which take place in traditional classroom context do not hinder learners from actively and meaningfully engaging the role of an expert naturally and realistically. The majority of the employers indicated that most fresh graduates are not ready to enter the job market as they lack the command of the English language, as well as communication skills and other workplace related skills. This paper presents how “E.X.P.E.R.T” role play technique is used in an academic English course classroom to address the concerns of workplace readiness among the fresh graduates. The researchers employed an in depth qualitative study through written reflections to capture the experiences, and insights of undergraduates at one of the Malaysian public universities. A total of nineteen learners from the Faculty of Health Sciences took part in this study. The findings indicate that E.X.P.E.R.T. technique promotes a more dynamic and up-to- date learning approach in equipping learners with the essential employability skills. It also highlights the teacher’s pedagogical role in employing the “E.X.P.E.R.T” role play technique.